New distribution records of Peruvian bats - Solari, Sergio (1999)
Based on recent collections and specimen reviews, we update data on the geographical distribution of ten bat species from Peru, and include some notes on their morphology, systematic status and ecology. These records include two latitudinal extensions (Lonchophylla robusta and Thyroptera lavali), and one altitudinal extension (Anoura latidens). Two species of Cynomops, paranus and planirostris, are both present in Peru and supported by our vouchers. Some misidentifications from previous papers are corrected and presented in their current taxonomic status. The diversities of bats from Jenaro Herrera and Cocha Cashu-Pakitza are corrected to 63 and 62 species, respectively.